Legal Protection of Child Victims of Human Trafficking (Human Trafficking) District in South Central Timor Review of Law Number 35 Year 2014 Regarding Child Protection - Evelyn bellatrix Sumbi; Irzani Andi Abdulrahman; Rahma Pramudya Nawang Sari; Arief Budiono (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
The increase in cases of human trafficking is a problem that has an impact on post-modern civilization. The uneven distribution of opportunities for education for the lower middle class has resulted in many cases of children dropping out of school due to higher education costs, uneven health services in various regions, and the influence of negative issues in the spotlight at home and abroad..In the eastern part of Indonesia, cases of human trafficking generally occur in rural communities with hidden recruitment by the perpetrators coming from the family environment and closest relatives as happened in South Central Timor, among others: Adoption of children who are not appropriate procedural and illegal; Culture (Oko Mama) and family; Become a worker with the promise of a large salary and a decent living; Approach through romance; and kidnapping of victims. Human trafficking cases, both domestically and abroad, are carried out with various modus operandi that are increasingly diverse and complex, so that a comprehensive and synergistic handling is needed. The results of research into criminal acts of human trafficking in East Nusa Tenggara must receive special handling from the government, law enforcement officials, families and communities so that they do not develop which have an effect on children. In addition, children must also receive attention both in growth and development in the community and in terms of education wherever they are and the social impacts that arise on lifestyle changes and on educational orientation..